Relationship Of Knowledge About Vaginal Discharge (Flour Albus) With An Attitude Of Maintaining The Cleanliness Of The External Genitalia While Vaginal Discharge (Flour Albus) Grade 5th And 6th In Elementary School 21 Sungai Raya - Indri Erwhani (Sekolah Tinggi Ilmu Keperawatan Muhammadiyah Pontianak, 2015)
Background: Puberty is a time of early sexual maturation. At this time, especially young women will menstruate. Most of the young women before or after menstruation will experience vaginal discharge (flour albus). Approximately 75% of women in the world would experience vaginal discharge (flour albus) at least once in a lifetime. Therefore, teenage girls need to understand about vaginal discharge (flour albus). When the young women experience vaginal discharge (flour albus) they will know how to maintain the cleanliness of their reproductive organs. By doing this it is expected to prevent the occurrence of abnormal vaginal discharge (flour albus) (pathological). Objective: To determine relationship of knowledge about vaginal discharge (flour albus) with an attitude of maintaining the cleanliness of the external genitalia while vaginal discharge (flour albus) grade 5th and 6th in Elementary School 21 Sungai Raya. Methods: This study is a correlation with the type of Cross-Sectional design, data collection technique using purposive sampling questionnaire, the subject of 47 respondents. Test analysis in this study is a statistical test Chi Square. Results: Analysis of bivariate with Chi Square shows there is a relationship of knowledge about vaginal discharge (flour albus) with an attitude of maintaining the cleanliness of the external genitalia while vaginal discharge (flour albus) grade 5th and 6th in Elementary School 21 Sungai Raya (ρ = 0,017). Conclusion: There is a relationship of knowledge about vaginal discharge (flour albus) with an attitude of maintaining the cleanliness of the external genitalia while vaginal discharge (flour albus) grade 5th and 6th in Elementary School 21 Sungai Raya